Foreign Investment, Supermarkets, and the Restructuring of Supply Chains: Evidence from Eastern European Dairy Sectors - Johan F. M. Swinnen; Liesbeth Dries; Nivelin Noev; Etleva Germenji (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
The combination of transition and globalization since the early 1990s has caused dramatic changes in supply chains globally. This paper uses survey evidence from several Eastern European countries (Albania, Bulgaria, Poland, Slovakia, Romania and Russia) on how these forces affect the dairy sector. In many countries dairy firms are small family firms. Investments by foreign companies in processing and retailing and the opening to international markets have introduced higher standards, leading, in turn, to extensive contracting and vertical coordination in the dairy chain. In countries close to the EU the restructuring of the dairy chain was mostly driven by investments in dairy processing, while in countries further from the EU, and less advanced in transition, retail investments are playing a more important role in driving change throughout the dairy chain. There have been significant efficiency gains, and the vertical coordination had positive effects on firm investments and productivity, especially since the late 1990s. Evidence suggests that small dairy firms have generally benefited from the vertical coordination processes.
Keywords: 330; Milchviehhaltung; Direktinvestition; Branchenentwicklung; Vertikale Konzentration; SB-Lebensmittelgeschäft; Polen; Albanien; Bulgarien; Slowakei; Rumänien; Russland